A rising incidence and poorer male outcomes characterise early onset paediatric inflammatory bowel disease. Issue 12 (27th April 2017) - Coughlan, A.; Wylde, R.; Lafferty, L.; Quinn, S.; Broderick, A.; Bourke, B.; Hussey, S.; ,
Summary: Background: The incidence of paediatric inflammatory bowel disease diagnosed before age 10 years is reportedly increasing, but national data are limited. Aim: To characterise the epidemiology, phenotype and clinical outcomes of children diagnosed with inflammatory bowel disease before age 10 years, and compare with data from children diagnosed aged 10‐16 years. Methods: A review of all Irish cases of early onset inflammatory bowel disease (diagnosis <10 years, EO‐IBD) presenting between January 2000 and December 2014 was undertaken and compared to a cohort of later onset paediatric inflammatory bowel disease patients (diagnosis between 10 and 16 years, LO‐IBD). Diagnostic investigations, phenotype, treatments, and long‐term clinical and surgical outcomes were analysed. Results: One hundred and ninety children (99 male) with EO‐IBD were identified; 92 (48%) CD, 77 (41%) UC and 21 (11%) IBDU. The incidence of EO‐IBD increased by 0.6 per 100 000 per year (0.8‐3.2 per 100 000 per year), with a significant increase in UC by 0.06 per 100 000 per year ( P =.02). Males with CD had more upper GI disease (L4a; 48% vs 21%; P =.007), more extensive disease distribution (L3±L4; 31% vs 11%; P =.05) and more severe disease activity at presentation (52% vs 31%; P =.05) than females. Fewer patients with early onset than later onset Crohn's disease had ileocolonic disease (L3; 10% vs 20%; P <.001). More relapses were observed in the first year post‐diagnosis in early onset than later onset IBD (1.02 vs 0.5 mean relapses; P <.001). Conclusions: EO‐IBD is increasing in incidence. Males have more extensive and severe disease phenotypes, and younger patients have higher relapse rates than older children. Further research to explain these findings is warranted. Abstract : Linked Content This article is linked to Wiskin and Sandhu, and Hussey papers. To view these articles visithttps://doi.org/10.1111/apt.14147 andhttps://doi.org/10.1111/apt.14192 .